Analysis of Demudification Drying of Peanut Seeds (Arachis hypogaea L.) and Identification of Seed Quality - Sholikah, Pipit Elok Nikmatus; Susilo, Bambang; Sutan, Sandra Malin; Damayanti, Retno; Hermanto, Mochamad Bagus (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
One strategy to increase peanut production is to use good-quality seeds. The content of the seed determines the quality of the seed. Drying with low relative humidity can lower the drying temperature so that drying is done quickly and seed quality is maintained. This research was conducted to analyze the process and differences in peanut seed drying using dehumidifier drying and oven drying methods. Drying was carried out using a dehumidifier and oven drying machine at 30 °C, 40 °C, and 50 °C until the moisture content reached 9%, with observations every 30 minutes. Then the dried seeds were analyzed for their physical and physiological qualities. The results showed that the time needed for dehumidifier drying was faster than oven drying, with the details of dehumidifier machine drying at 30 °C, 40 °C, and 50 °C being 18.5 hours, 15 hours, and 10.5 hours. While drying in the oven at the same temperature, it takes 21 h, 17 h, and 12 h. From the results of the analysis of the physical quality of the seeds, the germination test, and the vigor test, it can be seen that dehumidifier drying gave the highest seed percentage results of 98%, 98%, and 88%. Keywords: Dehumidifier, Drying, Peanuts, Seed Quality, Water content.